A prospective, open label, multicenter, postmarket study evaluating Princess VOLUME Lidocaine for the correction of nasolabial folds. Issue 6 (5th October 2020) - Kopera, Daisy; Ivezic‐Schoenfeld, Zrinka; Chang‐Rodriguez, Souyet; Hoeller, Sonja; Grablowitz, Doris; Bartsch, Katrin; Prinz, Martin
Abstract: The aim of this study was to investigate the safety and performance of Princess VOLUME Lidocaine in nasolabial fold correction. In this prospective, open label, multicenter, postmarket study subjects received injections of Princess VOLUME Lidocaine into both NLF at Baseline (Day 0) and if considered necessary by the investigator, at Week 2 (touch‐up treatment). This study was conducted in Austria at the Department of Dermatology and Venereology, Medical University of Graz, at the medical aesthetic center MÄZ WIEN, and at the medical aesthetic center Ordination Dr. Bartsch, Vienna. The 62 mainly female (95.2%) subjects had a median age of 52 years with two fully visible, approximately symmetrical NLFs, each scoring grade 2 or 3 on the nasolabial fold severity rating scale (NLF‐SRS) developed by Croma‐Pharma. The nasolabial fold severity was assessed by NLF‐SRS and Global Aesthetic Improvement Scale (GAIS) 4, 24, and 36 weeks later. Adverse events (AEs) were recorded throughout the investigation. With 95.1% of subjects showing an improvement of at least 1 grade of the NLF‐SRS at 24 weeks after the treatment, the primary endpoint was achieved, and clinical performance was demonstrated. Princess VOLUME Lidocaine was well tolerated, with only mild AEs, mainly injection site reactions, reported. Subject satisfaction (≥93.5%) and GAIS scores (≥93.5% improvement) were high. Princess VOLUME Lidocaine was effective in reducing NLFs as shown by an improvement in the severity of NLFs by at least one grade in 95.1% of subjects at Weeks 4 and 24.